Using infrared radiation in preparation of feed for farm livestock - T Senthilkumar; Ekaterina I. Reshetnik; Vyacheslav G. Evdokimov; Lyubov I. Perepelkina; Zoya F. Krivuca; Yulia R. Samarina; Evgeniy E. Kuznetsov; Natalia A. Kuznetsov (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The article in hand describes a processing line for preparation of feed for farm livestock and the design of an infrared drying unit integrated into this line. The main objective of this study is to find ways to provide a full-value feeding of farm animals throughout the calendar year.  At present, there are various methods for preserving feed proposed with the aim of providing a full-fledged diet.  However, following the recommendations for feed storage according to the recommended conditions, as a rule, results in high losses of its total weight and nutritional properties due to a long winter period with low-temperature regimes, typical of the Amur Region of Russia. This article presents the results of the study of a prospective processing line for the preparation of feed for long-term storage, which ensures the preservation of their basic nutritional properties, with an integrated infrared drying unit.